PENGARUH BUDAYA ORGANISASI DAN KEPEMIMPINAN TERHADAP EMPLOYEE ENGAGEMENT PADA PEGAWAI NEGERI SIPIL DI KANTOR BUPATI BAGIAN UMUM SETDA KABUPATEN SIAK - Anggreana, Viqi; Hendriani, Susi; Fitri, Kurniawaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted to determine the factors that affect the employee engagement. The factors studied were the effects of organizational culture and leadership. Collecting data this research used a questionnare survey. The questionnare was delivered to 44 goverment employees at general section in Regent Office Secretariat Region Siak District, total of 44 questionnares (100%) returned complete and can be processed . The data were analyzed by using with multiple linear regression with SPSS. The results of hypothesis testing is organizational culture and leadership have relation and significant to employee engagement. To improve employee engagement, organizations need to improve letting employees involved directly and give confidence to the employees to improve job satisfaction which would motivate the employees to work well, in addition the organization also must provide clear career paths and procedures payment they receive. While the culture of the organization to optimize The Regent’s Office Common Part Siak Secretariat Districts need to socialize the existing organizational culture. And for the leader, they should better understand the needs and desires of employee and are willing to listen to feedback and complaints of employees.Keywords: organizatinal culture, leadership and employee engagement